2007
DOI: 10.1111/j.1439-0531.2006.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insemination–Ovulation Interval and Addition of Seminal Plasma on Sow Fertility to Insemination of Cryopreserved Sperm

Abstract: In swine, the use of frozen-thawed (FT) sperm for artificial insemination (AI) is limited because of poor sow fertility, possibly associated with a post-thaw capacitation-like status resulting in fewer fully viable sperm. Sow fertility to AI with FT sperm may improve with deeper deposition of sperm within the female tract, insemination very close to ovulation, or reversal of cryocapacitation by seminal plasma (SP). We performed two experiments to examine these suggestions. In experiment 1, 122 multiparous York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…This fertility window is supported by other studies that show no differences in timing for cryopreserved sperm when inseminations occurred within a −12 to −2 h window relative to ovulation (Abad et al. ). Others have also reported timing of ovulation on cryopreserved boar sperm fertility (Bolarín et al.…”
Section: Timing Of Inseminations Relative To Ovulationsupporting
confidence: 70%
See 1 more Smart Citation
“…This fertility window is supported by other studies that show no differences in timing for cryopreserved sperm when inseminations occurred within a −12 to −2 h window relative to ovulation (Abad et al. ). Others have also reported timing of ovulation on cryopreserved boar sperm fertility (Bolarín et al.…”
Section: Timing Of Inseminations Relative To Ovulationsupporting
confidence: 70%
“…However, with frozen boar sperm, IUI allowed establishment of fertility but did not provide any clear advantage to fertility (Abad et al. ). This appears to be supported by other studies using two billion motile sperm, which resulted in a farrowing rate of 76% and 9.0 pigs born but with no clear advantage to using IUI (Chanapiwat et al.…”
Section: Alternative Insemination Approachesmentioning
confidence: 99%
“…Supplementation of seminal plasma to frozen-thawed boar spermatozoa has been reported to improve farrowing rates (Okazaki et al 2009) and litter size . While other studies have found no effects on fertility (Abad et al 2007a) or on the establishment of an oviductal sperm reservoir (Abad et al 2007b). The situation is similar in the ram where cervical insemination of frozen-thawed sorted or non-sorted ram spermatozoa has been reported to improve or Handling-induced sperm surface changes have no effect on field fertility (Maxwell et al 1999, El-Hajj Ghaoui et al 2007, O'Meara et al 2007, Leahy et al 2010b.…”
Section: Stabilisation Of the Sperm Surface With Seminal Plasma Proteinsmentioning
confidence: 86%
“…; Abad et al. ). When accompanying eCG‐induced oestrus, controlled ovulation resulted in 15% higher sow farrowing rates and this was maintained with single inseminations (Cassar et al.…”
Section: Controlling Oestrus and Time Of Ovulationmentioning
confidence: 98%